2007
DOI: 10.2478/v10007-007-0031-7
|View full text |Cite
|
Sign up to set email alerts
|

Nitroimidazoles. V. Synthesis and anti-HIV evaluation of new 5-substituted piperazinyl-4-nitroimidazole derivatives

Abstract: A series of 2-alkylthio-1-[4-(1-benzyl-2-ethyl-4-nitro-1H- -imidazol-5-yl)-piperazin-1-yl]ethanones (3-9) and alkyl-[4-(1-benzyl-2-ethyl-4-nitro-1H-imidazol-5-yl)-piperazin-1-yl)ketones (11-20) as well as the indole analogue 22 were synthesized from 4-nitro-5-piperazinyl imidazole derivative 1, with the aim to develop newly non-nucleoside reverse transcriptase inhibitors (NNRTIs). The newly synthesized compounds were assayed against HIV-1 and HIV-2 in MT-4 cells. Compound 4 showed inhibition of HIV-1 (EC50 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Al-Soud et al, reported the synthesis of new 5-substituted piperazinyl-4-nitroimidazole derivatives and their evaluation for anti-HIV activity [95]. The target was the synthesis of new 4-nitroimidazoles, leading to inhibition of HIV by inhibition of RT and reduction of the drug-resistance strains [95].…”
Section: Anti-hiv Active Nitroimidazolesmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-Soud et al, reported the synthesis of new 5-substituted piperazinyl-4-nitroimidazole derivatives and their evaluation for anti-HIV activity [95]. The target was the synthesis of new 4-nitroimidazoles, leading to inhibition of HIV by inhibition of RT and reduction of the drug-resistance strains [95].…”
Section: Anti-hiv Active Nitroimidazolesmentioning
confidence: 99%
“…The target was the synthesis of new 4-nitroimidazoles, leading to inhibition of HIV by inhibition of RT and reduction of the drug-resistance strains [95]. Compounds 25 and 26 were found to be most active among the tested compounds inhibiting HIV replication in cell culture ( Figure 5).…”
Section: Anti-hiv Active Nitroimidazolesmentioning
confidence: 99%
“…We present the synthesis 8-chloro-2,3-dihydroimidazole [1,2b] [1,4,2] benzodithi-azine-5,5-dioxides and 9-chloro-2,3,4-trihydropyrimido [1,2b] [1,4,2] benzodithi-azine-6,6-dioxides (figure 1). Succesfully identified anti-HIV activity ECO 50 0.09 μM.…”
Section: Imidazole Compound and Derivatesmentioning
confidence: 99%
“…In continuation for our attempts in searching for new anti-HIV agents, [15][16][17][18][19][20][21][22][23] and on the basis of above promising biological results, we considered benzimidazoles and their analogs particularly interesting to optimize the synthetic approaches to our antiviral agents. In this study, the angiotensin-converting enzyme (ACE) inhibitor 'captopril' 24 has been selected as a main backbone for the synthesis of new benzimidazole, benzothiazole derivatives and their analogs as well as the thioether-captopril analogs, utilizing microwave irradiation method.…”
Section: Introductionmentioning
confidence: 99%